Validity of the Land Sale and Purchase Agreement which is paid in full and carried out in good faith - Syahputrama, Rifky (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
PPJB is a preliminary agreement that is obligatory, so that it only creates an obligation to be carried out at a later date as outlined in the main agreement, namely AJB. PPJB does not yet provide for the transfer of land rights, so the ownership of the land object of sale and purchase has not yet passed from the land owner to the buyer. But in reality, there are still parties who consider that the PPJB has transferred ownership rights to the land. The purpose of this research is to analyse and identify the validity of PPJB that is paid in full and carried out in good faith and its legal consequences in Supreme Court Decision Number 3753 K/Pdt/2020 and to analyse and identify the legal protection of buyers in a sale and purchase binding agreement that is paid in full and carried out in good faith in the decision. The research method used is Normative Juridical, using positive law inventory research specifications, and finding law in concreto, using secondary data, and qualitative normative analysis. The results showed that the Panel of Judges of the Supreme Court had given a decision related to the problem, in which the Panel of Judges of the Supreme Court was of the opinion that the PPJB made between the Plaintiff and the Defendant before the Notary was a general agreement that had not transferred ownership rights, so that the AJB made between Defendant 1 and Defendant 2 before the PPAT was valid proof of transfer.